Design of a freeform lens for structured light illumination by deconvolution algorithm and feedback modification. (January 2019) - Ge, P; Zhang, K; Mao, L; Zhang, Y; Xu, H
In this paper, we propose a method combining a deconvolution algorithm and a feedback modification to design a freeform lens for structured light illumination. The deconvolution algorithm can alleviate the blur effect caused by the extended light source and the feedback modification can further improve the quality of the structured light by iteration. A lens for a linear sinusoidal pattern is designed by the proposed method. Simulation results show the contrast is 89%, compared to 57% achieved by the conventional design method.